Madame Marie Curie: Radioactivity and Atomic Energy - DHAR, N.R. (SCHOOL SCIENCE, 2006)
As late as 1895 physicists and chemists seemed to be convinced that the ultimate particles of matter consist of atoms which cannot be further broken down. In 1896, a new phenomenon, i.e., radioactivity, was discovered by Henri Becquerel (1852- 1908) of France, which changed our ideas regarding the ultimate particles of matter. The discovery of X-rays by Prof. Roentgen (1845-1923) in 1895, of cathode rays by J. Plucker (1801-1868) and others also helped in modifying the scientists’ notion regarding the atom.